The ironic hypotheses in the Iraqi narrative are a procedural entry - matrud, Karim Shgidl (Al-Adab Journal, 2015)
This research phenomenon of sarcasm in the arts of narrative Iraqi ( story and the novel ) , that cynicism is not just a style of satirical harassed the other or just formulations linguistic contradictory or metaphor expressionistic be a word which is contrary to the indication , it is a method and mechanisms and technical implications and connotations , and we have found that the phenomenon occupies Area broader pan speeches cultural , intellectual , literary and artistic , so that myths and legends and folk tales , stories and novels have been built mostly on relationships sarcastic for pairing between reality and fantasy , the style of sarcasm before the approach rhetorical can touch patterns in poetry or scripture , is a phenomenon structural texts legendary myths, we have tried in this research memorize the technical basis for this phenomenon through the application of cash on Onmozgen of narrative contemporary Iraq , namely: ( ancestors somewhere ) collection of short stories by Saad Hadi , and a novel (BBA Sartre ) Ali Badr , as well as reference for many of the models built on the foundations of sarcasm .